KAJIAN â€˜URF PADA PENOLAKAN SERTIFIKASI HALAL MUI TERHADAP PENAMAAN PRODUK BERLABEL SETAN - Siti Nur Faiza (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2021)
This research is the result of field research to analyze the 'urf study on the rejection of the MUI halal certification of naming â€œdevil noodle productsâ€. In conducting research, the author uses qualitative methods by using field data and complemented by secondary data to strengthen the analysis that comes from previous research, books, journals, decrees, and others. Then, uses descriptive analysis techniques to analyse. Noodle devil is one of the spicy culinary foods that has a lot of customers but in its business journey this product did not get approval to get the halal label of the East Java MUI because the devil's name does not match "SK 46 / Dir / LPPOM MUI / XII / 14 and Fatwa MUI Number. 4 of 2003 concerning Standardization of Halal Fatwa. "Although the devil's noodle product has been known to mean spicy noodles with a level of spiciness, the custom of using the name Setan includes urf 'lafzi which is unacceptable because the word Setan is included in the category of names of Allah's enemies who are feared to keep them from remembering Allah. Based on the validity of the â€˜urf namingâ€™ of products labeled satanic, including â€˜urf fasidâ€™ which must be abandoned. From the results of the research, LP POM MUI East Java is very careful in accepting or rejecting applications for Halal Product Certification, the first step of the East Java LPPOM MUI is to assess the name or symbol on the product being proposed. If Surabaya devil noodle sellers want to get the halal label from the East Java MUI, they must change the devil's name to a good name and symbol that not lead to kufr and forget to remember Allah.